2023
DOI: 10.3389/fneur.2023.1189746
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model, miRNA-TF network, related subgroup identification and drug prediction of ischemic stroke complicated with mental disorders based on genes related to gut microbiome

Abstract: BackgroundPatients with comorbid schizophrenia, depression, drug use, and multiple psychiatric diagnoses have a greater risk of carotid revascularization following stroke. The gut microbiome (GM) plays a crucial role in the attack of mental illness and IS, which may become an index for the diagnosis of IS. A genomic study of the genetic commonalities between SC and IS, as well as its mediated pathways and immune infiltration, will be conducted to determine how schizophrenia contributes to the high prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%